A Study of the Impact of the Climate and Land-use/Land-cover (LULC) Changes on the UAE Mangrove Forests over the Period 1990-2020 - Raihan, Asif (2023)
A Master of Science thesis in Civil Engineering by Asif Raihan entitled, “A Study of the Impact of the Climate and Land-use/Land-cover (LULC) Changes on the UAE Mangrove Forests over the Period 1990-2020”, submitted in June 2023. Thesis advisor is Dr. Tarig Ali and thesis co-advisor is Dr. Md. Maruf Mortula. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).